Editorial (Revista de Divulgación Shimmering Words: Research and Pedagogy E-Journal, 2021)
People around the world are living an age of change, the pandemic situa tion (Covid 19) appeared and made peo ple alter their habits and customs; every body should take different decisions in order to act out to the new needs; our purpose in this volume is to take care of health without stopping work and study; However, we realize, it has not been an easy task for many of the population around the world.In the Education field, we can see different situations, for instance, mi llions of children and young people are confined to study and work from home. Doctors, psychologists, professors, and pedagogues (2004)2 state that children and young people are social living be ings who need the interactions in order to build their personality and acquire habits which are a need to live in society. Hence, the circumstances of the pande mic situation could have serious psycho logical and behavioral repercussions on this population.On the same hand, higher educa tion faces big challenges generated by the situation of confinement; for exam ple, the Internet connection, methodo logies through digital tools, teachers and students' training to develop virtual clas ses, appropriate resources that motivate and provide learning. There are many aspects to analyze and highlight during this pandemic situation and specially inthe Educational field. What is perceived is that education is experiencing many changes in short time, and many of them will remain after the confinement.Despite the difficulties that we have been experiencing experience, it is time to take advantage of the use of technology to innovate with virtual tools that can con tribute to improve out teaching and lear ning practices. Many tools and resources have risen in different web pages; thus, it is important explore and include them as support on teaching in different areas of knowledge. All what we can explore and learn using digital tools is profit in the im provement of education.Finally, something to stand out in the virtual work is the teamwork. Some times we do not know what are the most suitable digital tools to work in our field of study, the best option is to ask our partners, classmates, mates and anyone else; teachers can help each other from their own experience. It is expected that digital tools facilitate teachers and stu dents' work, contribute to overcome lear ning problems, and improve academic processes.
Keywords: campo de educación; trabajo virtual